Twenty-Eighth International Congress on Large Dams/Vingt-Huitième Congrès International Des Grands Barrages - ICOLD / CIGB (CRC Press, 2025)
The International Commission on Large Dams (ICOLD) held its 28th International Congress in Chengdu, China (16 May – 23 May 2025). The proceedings of the congress focussed on four main questions (Questions108-111): 1. Dams and reservoirs for climate change adaptation; 2. Dams and levees fit for the future; 3. Safety of dams and levees facing extreme hydrological events, and 4. Earthquake performance and safety of dams. The book thoroughly discusses these questions and is indispensable for academics, engineers and professionals involved or interested in engineering, hydraulic engineering, and related disciplines.La Commission Internationale des Grands Barrages (CIGB) a tenu son 28e Congrès International à Chengdu, Chine (16 mai - 23 mai 2025). Les actes du congrès portent sur quatre questions (Questions 108-111) principales : 1. Barrages et réservoirs: adaptation aux changements climatiques; 2. Des barrages et des digues prêts pour l'avenir; 3. Sécurité des barrages et des digues lors des évènements météorologiques extrêmes, et 4. Performance sismique et sécurité des barrages. Le livre traite en profondeur de ces questions et est indispensable pour les universitaires, les ingénieurs et les professionnels impliqués ou intéressés par l'ingénierie, l'ingénierie hydraulique et les disciplines connexes.